(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the perception and practical experiences of Doulas on obstetric violence and the main intervention actions to reduce it. Methods: Qualitative study, with 11 Doulas, identified by D1 to D11 and asked with questions that referred to perceptions of knowledge about obstetric violence, which practices are evidenced throughout the activity, which practices they believe have more impact on reducing violence obstetric and what attitudes were taken to try to reduce them, in addition to the reception of the multidisciplinary health team regarding the intervention of Doula at the time of delivery. The results were analyzed according to the principles of qualitative assessment. Results: The work was developed along 3 axes: obstetric violence in the daily practices of the doulas, effective actions to reduce obstetric violence and the multidisciplinary team’s receptivity to the Doulas’ interventions. According to the forms, all the doulas show obstetric violence, with episiotomy, Kristeller’s maneuver, verbal violence and repetitive vaginal touches being the most cited in the study. As for the receptivity of the team, it was evidenced that it suffers interference from the lack of knowledge about the exact function of doulas, overlapping with other professionals. The fundamental instrument in combating obstetric violence is to provide pregnant women with information about childbirth. Conclusion: The work showed the importance of Doulas associated with obstetric physiotherapy practices as an agent in the humanization of childbirth and the reduction of obstetric violence, requiring further studies with this focus group, aiming at the importance of the topic and its literary scarcity.